Statistical thermodynamics - Gupta, M. C. (New Delhi : New Age, 1998)
This Is An Introductory Book Which Explains The Foundations Of The Subject And Its Application. It Is Intended Primarily For Graduate Students But May Provide Useful Information And Reading To Science And Engineering Students At All Levels. It Assumes That Readers Have Knowledge Of Basic Thermodynamics And Quantum Mechanics. With This, The Theory Has Been Developed In A Simple, Logical And Understandable Way. Some Applications Of Statistical Thermodynamics Have Been Described In Detail With Illustrative Solved Examples.There Are Two Basic Approaches In Statistical Mechanics; One Based On The Study Of Independent Particles In An Isolated System And The Other Based On The Concept Of Ensembles. In This Book Attempt Has Been Made To Take Advantage Of Both Approaches. While The Fundamental Concepts Have Been Developed By First Approach, Concept Of Ensembles Have Been Included To Bring Out The Importance Of This Concept In The Application Of Statistical Thermodynamics To Chemical Systems Where Interparticle Interactions Become Important.Part I Of The Book Deals With The Background Concepts, Fundamentals In Mathematics, Classical Mechanics, Quantum Mechanics And Thermodynamics Which Are Essential For Statistical Mechanics. Part Ii Covers Formalism Of Statistical Mechanism And Its Relation To Thermodynamics As Well As The Statistical Mechanics Of Ensembles, Quantum Statistics And Fluctuations. Part Iii Includes Chapters On The Applications Of The Formalism To Real Laboratory Chemical Systems. In This Part Additions Such As Imperfect Gases, Equilibrium Isotope And Kinetic Isotope Effects And Reactions At The Surfaces Have Been Made, In This Edition. Part Iv Is Also An Addition Which Covers Quantum Systems Such As Ideal Fermi Gas (Free Electrons In Metals), Photon Gas And Ideal Bose Gas (Helium Gas).
Appendix 492-501p. ; Include bibliographical references; Index 503-507p.
Keywords: Kinetic theory; Liquid state; Quantum mechanics; Statistical thermodynamics; General Science